Collection of Fáfia [Pfaffia glomerata (Spreng.) Pedersen] in Northwestern State of Paraná - Brazil - Ming, Lin Chau [UNESP]; Correa, C. [UNESP] (My University, 2002)
Interviews were conducted with fáfia (Pfaffia glomerata (Spreng.) Pedersen) collectors from the municipal districts of Querência do Norte and Porto Rico, where enterprises and buyers of this plant are concentrated. The results allowed us to conclude that both the adults and children make collection. Each adult collects from 50 to 150 kg of roots/day, depending on the collection area, for about 8 months/year. Collections mostly occur all over the year, but the activity becomes more intense from May to August. All families are not exclusively dedicated to fáfia collection and also develop other rural activities. They have been collecting fáfia for 2 to 13 years, indicating that an intensive exploitation has been present in the region for over a decade. During collection, no plant part is used for replanting the species. The roots are commercialised by regional buyers. The price of the roots varies from US $ 0.07 to US $ 0.13/kg and average gain is about US $ 2,055/family/year, representing a considerable profit for the collectors.
Keywords: Collection of plants; Domestication; Endangered species; Exploitation of natural flora; Genetic conservation; Medicinal plant; Socio-economic survey